Lipoteichoic Acid Inhibits Interleukin-2 (IL-2) Function by Direct Binding to IL-2 - Plitnick, Lisa M. (American Society for Microbiology, 2001)
Lipoteichoic acid (LTA) is associated with the cell envelope of most gram-positive bacteria. Although previously thought to act mainly as a virulence factor by virtue of its adhesive nature, evidence is now provided that LTA can also suppress the function of interleukin-2 (IL-2), an autocrine growth factor for T cells. LTA from four separate bacterial strains lowered the levels of detectable IL-2 during a peripheral blood mononuclear cell response to the antigen tetanus toxoid (TT). T-cell proliferation in response to TT was similarly inhibited by LTA. In contrast, levels of detectable gamma interferon increased. In addition, LTA inhibited IL-2 detection by enzyme-linked immunosorbent assay (ELISA) and blocked the proliferative response of an IL-2-dependent T-cell line to soluble IL-2. Further studies using ELISA demonstrated that LTA blocks IL-2 detection and function by binding directly to IL-2. Flow cytometric analysis revealed that IL-2 binding to T cells is inhibited in the presence of purified LTA but not LTA plus anti-LTA monoclonal antibody. In summary, these studies demonstrate a novel effect of LTA on the immune response through direct binding to IL-2 and inhibition of IL-2 function. Importantly, gram-positive organisms from which LTA is obtained not only play an important role in the pathology of diseases such as bacterial endocarditis, septic shock, acute respiratory distress syndrome, and multiple organ failure but also comprise a significant portion of commensal populations within the human host. Inhibition of IL-2 function by LTA may represent yet another mechanism by which gram-positive bacteria dampen the host immune response and facilitate survival. Thus, LTA provides a potential target for therapeutic intervention when gram-positive organisms are involved.